Molecular and morphometric identification of pistachio psyllids with niche modeling of Agonoscena pistaciae (Hemiptera: Aphalaridae). Issue 2 (27th April 2020) - Lashkari, Mohammadreza; Burckhardt, Daniel; Shamsi Gushki, Roghayeh
Abstract: Species of Agonoscena (Hemiptera: Aphalaridae) are key pests of pistachio in all of the most important pistachio producing countries in the Old World. The efficiency and accuracy of DNA barcoding for the identification of Agonoscena species were tested using mitochondrial cytochrome c oxidase subunit 1 ( mtCO1 ) and cytochrome b ( cytb ) gene sequences. Moreover, morphometric sexual dimorphism was studied. Finally, the potential geographical distribution of Agonoscena pistaciae, the most important pistachio pest, was calculated using the MaxEnt model. Similar relationships of clustering were found in the morphometric analysis and the molecular analyses with mtCO1 and cytb genes, with A. bimaculata and A. pistaciae being closely related, and A. pegani constituting their sister group. Although the results showed that the cytb gene is a better marker for barcoding in this group, the mtCO1 gene clearly separates the three psyllid species making mtCO1 suitable for diagnostic purposes. A geometric morphometric analysis showed that the distance between landmark number 7 (bifurcation of vein M) to the fore margin of the forewing, and the distance between landmarks number 6 (apex of vein Cu1b ) and 11 (wing base), are the most important geometric characters for diagnosing the studied species. Moreover, the forewing shape of males vs females is similar in A. pistaciae and A. bimaculata but differs significantly in A. pegani . In the ecological niche modeling of the distribution of A. pistaciae, the most important contribution was made by the variable 'minimum temperature of coldest period'. The most suitable areas for A. pistaciae are restricted to Eastern, Southern and some parts of Central Iran.